THE PHENOTYPIC PERFORMANCE OF KAMBRO CROSSBREEDS OF FEMALE BROILER COBB 500 AND MALE PELUNG BLIRIK HITAM - Mahardhika, I Wayan Swarautama; Daryono, Budi Setiadi (Buletin Veteriner Udayana, 2019)
This research was conducted to measure the phenotypic performance of Kambro crossbreeds of Pelung Blirik Hitam and Broiler Cobb 500. Based on Body Weight (BT) measurement, Kambro population (n = 17) has an average BT of 1,244.14 ± 453.82 grams significant (p <0.01) to F 1 Pelung (n = 7) with an average BT of 602.88 ± 79.93 grams in 8 weeks period with ad libitum diet of standard feed. Phenotypic performance of Kambro significant to F 1 Pelung based on the measurement of linear bodyweight parameter, vitality parameter, PPa-PBe parameter and phenotype parameter. Kambro has the phenotype combination of parental generation based on phenotype parameter. PPa parameter was suitable BT estimation model based on non-linear quadratic regression (r = 0.956) with formula 1.84E3 ±3.54E2*x+31.73*x 2 . Difference between chicken group (p<0.014) was significant to BT and interaction between group and linear bodyweight parameter was not significant based on Analysis of Covariance. The mortality rate of Kambro was lower than F 1 Pelung with the absent of vaccination in semi-intensive rearing system. As the size of hybrids population was limited, research findings must be validated with larger population size of hybrids.